INSTALLATION INSTALLATION OF LOCAL WISDOM VALUES OF BAJAWA ETHNIC AND SOCIAL ATTITUDES IN SOCIAL STUDIES LEARNING AT SMP NEGERI 3 WEST GOLEWA - fengi, anastasia alwinda; Suastika, I Nengah; Mudana, I Wayan (Academic Journal of Educational Sciences, 2024)
This research was conducted at SMP Negeri 3 West Golewa and aims to (1) Find out the local wisdom values ​​of the Bajawa ethnic group and the values ​​of social attitudes that can be instilled in social studies learning. (2) what is the strategy for cultivating the local wisdom values ​​of the Bajawa ethnic group and the values ​​of social attitudes in social studies learning. (3) knowing the results of instilling Bajawa ethnic local wisdom values ​​and social attitude values ​​in social studies learning. This research uses descriptive qualitative research to instill the local wisdom values ​​of the Bajawa ethnic group and the social attitude values ​​of students at SMP Negeri 3 West Golewa in social studies learning which were collected through observation, interviews and documentation. Data analysis used the Miles and Huberman model which consists of data collection, data reduction, data display and drawing conclusions or verification. The research results show that (1) the social and cultural values ​​contained in the local wisdom values ​​of the Bajawa ethnic group are reba, zono and kusu bue. The teacher's ability to provide examples of good interaction attitudes to students in the classroom and outside the classroom (2) the relationship between local wisdom values ​​and social attitude values ​​towards SMP Negeri 3 West Golewa social studies material,. (3) The teacher seems to have succeeded in instilling social attitude values ​​in accordance with the indicators that the researchers have described, namely: honesty, courtesy, self-discipline, tolerance in students at West Golewa 3 Middle School.